2020
DOI: 10.1021/acsomega.0c03456
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Liposomal β-Caryophyllene (Rephyll) by Nanofiber Weaving Technology and Its Effects on Delayed Onset Muscle Soreness (DOMS) in Humans: A Randomized, Double-Blinded, Crossover-Designed, and Placebo-Controlled Study

Abstract: Delayed onset muscle soreness (DOMS) is a complex spreading out, which is related to swelling of muscles, tenderness, rigidity, pain, disruption of muscle fiber, alteration in the kinematics of joint, acute tissue damage, and reduction in power and strength. β-Caryophyllene (BCP), a potent phytocannabinoid, could play an important role in managing DOMS because of its wide diversity of biological activities, particularly its anti-inflammatory activity; however, its poor stability in light, temperature, high vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 57 publications
(145 reference statements)
0
9
0
Order By: Relevance
“…This reveals the good encapsulation of AA into the nanofiber-stabilized liposomes due to the incorporation of AA into the phospholipids . The DSC spectrum of Zeal-AA shows the phospholipid melting point as a minor endothermic peak at 83 °C , and likeness associated with the vaporization of bounded and unbounded water molecules . The main exothermic peaks at 193 °C are due to the dissociation of phospholipid–AA cooperative forces (van der Waals forces and H-bonding) .…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…This reveals the good encapsulation of AA into the nanofiber-stabilized liposomes due to the incorporation of AA into the phospholipids . The DSC spectrum of Zeal-AA shows the phospholipid melting point as a minor endothermic peak at 83 °C , and likeness associated with the vaporization of bounded and unbounded water molecules . The main exothermic peaks at 193 °C are due to the dissociation of phospholipid–AA cooperative forces (van der Waals forces and H-bonding) .…”
Section: Resultsmentioning
confidence: 85%
“…The TEM images exhibit a distinct dark gray interface inside and a well-rounded transparent phospholipid layer, while the inner portion is seen to be darker, which is ascribed to the fastening effect of TNF. 20 The TEM and SEM of Zeal-AA reveal the formation of true liposomal products with a smooth surface and spherical shape without any accumulation, specifying the stability of the formulation. 2.3.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…BCP is present in essential oils at concentrations of 20% for clove bud oil, 20% for basil oil, 16% for oregano oil, 15% for hop oil, 11% for cinnamon oil, 8% for rosemary oil, 7% for black pepper oil, and 5% for lavender oil (20,21). A clinical study related to BCP has also been reported (22).…”
Section: Effects Of Inhaled β-Caryophyllene On Vascular Stiffness In ...mentioning
confidence: 99%